2020
DOI: 10.1016/j.ijrobp.2019.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Trial of Neoadjuvant FOLFIRINOX and Intensity Modulated Radiation Therapy Concurrent With Fixed-Dose Rate-Gemcitabine in Patients With Borderline Resectable Pancreatic Cancer

Abstract: Preoperative therapy in borderline resectable pancreatic cancer (BRPC) is intended to increase R0 resection rates. An optimal approach in BRPRC is not yet defined. We conducted a phase 2 trial in 25 patients with BRPC treated with Purpose: Preoperative therapy in borderline resectable pancreatic cancer (BRPC) is intended to increase R0 resection rates. An optimal approach in BRPC is yet to be defined. Methods and Materials: Patients with BRPC, confirmed adenocarcinoma, performance status 1, and adequate organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Murphy and colleagues report the potential benefit of neoadjuvant fluorouracil, leucovorin, oxaliplatin, and, irinotecan (FOLFIRINOX) and losartan followed by surgical resection in a phase II clinical trial. Of the 49 enrolled patients, 42 underwent attempted surgery and an R0 (margin-negative) resection was achieved in 69% (CI 55%-82%) (25). With neoadjuvant therapy, overall median progression-free survival increases to 17.5 months and overall survival to 31.4 months, although control outcomes were not given (24).…”
Section: Diagnosis Of Pancreatic Adenocarcinomamentioning
confidence: 99%
“…Murphy and colleagues report the potential benefit of neoadjuvant fluorouracil, leucovorin, oxaliplatin, and, irinotecan (FOLFIRINOX) and losartan followed by surgical resection in a phase II clinical trial. Of the 49 enrolled patients, 42 underwent attempted surgery and an R0 (margin-negative) resection was achieved in 69% (CI 55%-82%) (25). With neoadjuvant therapy, overall median progression-free survival increases to 17.5 months and overall survival to 31.4 months, although control outcomes were not given (24).…”
Section: Diagnosis Of Pancreatic Adenocarcinomamentioning
confidence: 99%
“…On the other hand, effective chemotherapy may lead to more adverse events. There is a report that NAT with FFX followed by IMRT concurrent with fixed-dose-rate GEM in BR-PDAC is feasible and tolerated [ 18 ]. Therefore, the IMRT technique may enable the application of NACRT in combination with more effective chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies reported outcomes for BRPC patients specifically. [22][23][24][25][26][27][28][29][30][31][32][33] Three studies also or solely reported outcomes for patients with resectable pancreatic cancer. [34][35][36] In total, the FOLFIRINOX alone studies included 310 patients (88.3%) with BRPC and 41 patients (11.7%) with resectable pancreatic cancer, whereas all 161 patients (100.0%) in the FOLFIRINOX with radiotherapy studies had BRPC.…”
Section: Included Studiesmentioning
confidence: 99%